Pengaruh Kadar Filler ZnO, Plasticizer Gliserol Dan Nisbah Air Terhadap Sifat Dan Morfologi Bioplastik Berbasis Pati Sagu - Syahputra, Annur Fauzi; Bahruddin, Bahruddin; HS, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The need of plastic as plastic bags, food or goods packaging progressively increasing. Bioplastics is one alternative to conventional plastics that are harmful to the environment.one of the ingredients that can be used as bioplastics is starch, but starch-based bioplastics are still lacking at the mechanical properties. The purpose of this study was to determine thecharacteristics of sago starch, determine the effect of water ratio, the composition of the ZnO filler and plasticizer glycerol on mechanical properties and morphology of bioplastics. Sagostarch was tested for the composition of amylose and amylopectin, while the bioplastics is tested for mechanical properties such as tensile strength (tensile strenght), elongation, wateruptake, biodegradation, and dispersion of the filler through SEM (Scanning Electron Microscopy) and analyzed using Response Surface Methodology (RSM) , Significance levelused in this study is 0.05 so that the most significant variables can be determined from pvalue value of <0.05 and a lack of fit> 0.05, which indicates that the model according to theresearch results. The factors that most significantly influence all responses are ZnO filler composition and followed by the plasticizer and water ratio. Best results are obtained on thecomposition of 15% filler, plasticizer 10% and the ratio of water 100 ml with a tensile strength of 15.484 MPa, elongation 2.691%, water uptake 28%, and 22.12% biodegradation.Key Words : bioplastics, filler ZnO, glycerol, starch, biodegradation